Effects of health education using mobile technologies on caregivers’ knowledge of routine growth monitoring for children aged 9 to 24 months in Kenya - Justus O. S. Osero; Edna N. Osano (Cogent Public Health)
Routine growth monitoring (RGM) for 9 to 24-month-old children enables early detection of developmental problems for corrective interventions. Unfortunately, many caregivers cease active RGM activities once they exhaust the government-recommended vaccines. The study aimed to find out the effects of health education using mobile technologies on caregivers’ knowledge of RGM. The study was quasi-experimental in design. Caregivers in interventional arm 1, received health education (HE) messages sent via a Short Text Message (STM). Caregivers in interventional arm 2, received HE messages using Voice Calls (VC). Control arms received the usual care. Post-intervention results revealed that there was an increase in the number of respondents who knew the importance of RGM for their children. Post-intervention analysis showed that caregivers in intervention arms 1 and 2 were more presumably to know when their children should be taken for RGM (OR = 3.000; 95% CI: 2.098 – 4.29), what is done during RGM visits to a child welfare clinic, the benefits of RGM, and problems associated with failure to engage in RGM compared to those in the control arm and at the beginning of the study. Health education using mobile technologies improved caregivers’ knowledge of routine growth monitoring.